Development of Interactive Multimedia Based on Articulate Storyline for Force Material to Improve Learning Outcomes - Nurkhalimah, Adinda Inka; Andriani, Aldina Eka (FKIP - Universitas Riau, 2025)
This study aims to describe the development, feasibility, and effectiveness of interactive multimedia based on Articulate Storyline to improve fourth-grade students' learning outcomes at SDN Purwoyoso 01, Semarang. The research follows the Research & Development (R&D) method using the Borg and Gall model. Data collection techniques include tests (pre-test and post-test) and non-test methods (observation, interviews, questionnaires, and documentation). Data analysis involves normality tests, t-tests, and N-Gain tests. The developed multimedia consists of a main page, guidelines, learning materials, instructional videos, a virtual laboratory (PhET Simulation), interactive quizzes (Quizizz), and student worksheets (Live Worksheets). Feasibility assessments showed high validity from material experts (93.75%), media experts (93.33%), teacher responses (100%), and student responses (98.80%), categorizing it as highly feasible. The effectiveness was demonstrated by a 26.40% increase in pre-test and post-test scores, a paired sample t-test significance value < 0.001, indicating a significant difference, and an N-Gain score of 0.728 (high category). In conclusion, the interactive multimedia was successfully developed, deemed feasible, and proven effective in enhancing fourth-grade IPAS students' learning outcomes on force material at SDN Purwoyoso 01, Semarang.